Tindak Tutur Guru TK Noor Annisa Di Desa Dirgahayu Kabupaten Kotabaru dalam Proses Belajar Mengajar - Rudy Suryana (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this research is to know the forms of speech acts used by the teacher at Noor Annisa Kindergarten by referring to the politeness principle and the principle of cooperation and to know the application of politeness principles and the principle of cooperation in the speech acts used by Noor Annisa's kindergarten teacher. The method used in this study is a qualitative research method that is descriptive in that it describes objectively and actual stages of teacher speech acts in the learning process. While this type of research is linguistic research with a purposive sampling method. Purposive sampling is a sampling technique for certain considerations based on meeting information needs. The results of the study show the form of teacher speech acts in interacting with students during the learning process with politeness principles and the principle of cooperation in the form of reprimand, advice, orders, warnings, cooperation with researchers, requests, and requests for cooperation with colleagues. While the application of speech acts between teachers at Noor Annisa Kindergarten is in the form of actions taken by the teacher when the learning takes place, by slowing down the return of students who do not follow the rules before going home, for example sitting neatly and not noisy, separating noisy students by ordering them sit in certain places, and postpone learning activities to discipline students by making them realize their mistakes. Keywords: Kindergarten teacher's speech, politeness principle, and cooperation principle